Karakteristik Klinik dan Analisis Faktor Risiko yang Berperan pada Derajat Keparahan Invasi Plasenta Abnormal di RSUP Persahabatan pada Tahun 2015-2018 - Feharsal, Yuri; Lisnawati, Yuyun; Pudyastuti, Sri; Khonsa, Oni; Apriliawan, Tri; Botefilia, Botefilia; Nurfauziah, Nadia; Agustin, Kindy (Majalah Kedokteran Indonesia, 2019)
Background: Morbidly adherent placenta is a condition which placenta adheres and invades deeply into the myometrium and, in some cases, until uterine serosa, thus contribute to peri-partum hemorrhage and significant maternal mortality.Purpose: To identify prevalence, clinical characteristics and their odds ratio to increasing se-verity of morbidly adherent placenta case in RSUP Persahabatan from 2015 to 2018.Methods: Cohort retrospective study.Results: From 2015 to 2018, prevalence of morbidly adherent placenta was around 0.8%. The risk factors which contribute to increasing severity of morbidly adherent placenta were: age above 35 years (OR 1.6, 95% CI 0.41-6.24) and history of Caesarean section more than 2 times (OR 1.63, 95% CI 0.41-6.46). The presence of increasing severity of morbidly adherent placenta were related to volume of blood loss more than 1000 ml during surgery (OR 2.13, 95% CI 0.52-8.76). Conclusion: The prevalence of morbidly adherent placenta at Persahabatan General Hospital in 2015-2018 was 0.8%. Age, history of Caesarean section more than 2 times, volume of blood loss, and duration of surgery were not statistically associated with adherent placenta case.